A qualitative analysis of the implementation of integrative medicine standards and protocols as a way of accessing the right to life and health in Brazil (Research, Society and Development, 2022)
The implementation of a system based on conventional medicine involves high investment, generating difficulties in implementing the system in countries with fragile economies and, consequently, with serious public health problems. To minimize the public health problem in the world, the World Health Organization (WHO) created guidelines for the implementation of public policies, integrative and complementary health protocols, based on knowledge of popular culture, with low cost, enabling global access to health. The objective of the study is to understand the implementation and effectiveness of integrative and complementary health practices (PICS) by the SUS, including contractual aspects with supplementary health operators. This is a qualitative study, which adopted as methodology the explanatory review of the literature and judicial decisions of the Courts of Justice of São Paulo (TJSP) and Minas Gerais (TJMG). The Brazilian constitutional system has adopted citizens' access to comprehensive health as a fundamental right, therefore, comprehensiveness is not limited to conventional medicine care. Integrative and complementary medicine works on the person's physical, mental and intellectual well-being. Of the 5,570 Brazilian municipalities, 77.15% have the provision of PICS in the primary care network of the Unified Health System, however, the implementation of the system presents problems of training and partiality of offer, requiring the enactment of specific legislation so that the PICS are also adopted by supplementary health. The TJSP and TJMG, in cases of judicialization, have issued decisions determining the cost, by the health plans, of treatments based on PICS.